Comparison of Different Volatility Model on Dhaka Stock Exchange (Global Journal of Science Frontier Research, 2017)
Dhaka stock exchange (DSE) is a very hazardous market, so its volatility forecasting would be a very difficult and necessary task. The behaviour of Stock Market is different from market to market. So a unique time series model couldn’t be a best forecasting technique for all stock market because of their varying nature. There are various types of time series model like Expected weighted moving average model, GARCH-type models, Moving Average models, Exponential smoothing model and so on. In this paper our objective is to compare the ability of different types of models to forecast volatility of Dhaka stock exchange.
Keywords: DSE; volatility; forecasting; model comparison